Direct effects of protective cladding material on insect pests in crops. (July 2019) - Fennell, Joseph T.; Fountain, Michelle T.; Paul, Nigel D.
Abstract: Current horticultural crops are increasingly grown under protective plastic claddings. These have historically been used to protect crops from abiotic stresses, however new challenges are emerging that present opportunities for innovative control technologies. Protected cropping already provides a favourable environment for pest and disease establishment. Coupled with high labour costs, restrictions in pesticide approval and introductions of new invasive species, development of new pest and disease control methods is of paramount importance. Claddings have been formulated to change the properties of solar illumination in the crop environment with wide ranging implications for crop, pest and pathogen. Properties that interfere with pest behaviour, leading to disrupted host location and lower pest load, can be exploited as part of an Integrated Pest Management system. This review provides a state-of-the-art summary of the field and laboratory studies that have focused on the direct effects of UV-attenuating film claddings on insect pests. It relates this to insect vision and the likely mechanisms of pest control. Ultimately, it provides a useful synthesis of the research completed to date, and recommends future research and agronomy directions. Highlights: We bring together all field studies of pests and UV-attenuation. Hemiptera and Thysanoptera were consistently suppressed by partially UV-blocking claddings. Future research should focus on less studied orders such as Diptera. We present recommendations for making research more comparable between studies.